Airport Company Leadership Communication Style as A Coach in the Era of Change - Mulyana, Ahmad; Sugyanto, Ricko (International Research Journal of Business Studies, 2021)
This article describes an adaptation of the leadership communication style in the pandemic era to maintain business continuity. The analysis uses the theory of change, organizational communication, and leadership. The method used is a case study with a qualitative approach where data mining is carried out through in-depth interviews, observation, and documentation. The study results concluded that the leadership style applied as a communication pattern as a coach with employees to maintain business continuity. Through this pattern, the nature of the partnership with employees is well established. This research has implications for efforts to prioritize the leader’s communication competence as Coach leadership style in implementing changes during the Covid-19 pandemic. The study results show that the role of the leader as a Coach can raise employee awareness to understand and accept changing conditions and have a commitment to take actions that can maintain the company’s business continuity.